Time Domain Response of Uniform RC Lines with RC Termination at Both Ends - Muhammad Taher Abuelma'atti (Active and Passive Electronic Components)
The time domain response of uniform RC lines with RC termination at both ends is obtained from the approximate poles of the transfer function. A simple model is developed for the URC line. The model consists of three passive elements only and can be easily implemented for computer-aided analysis of URC lines with RC termination at both ends.